Bcpks12 gene inactivation substantiates biological functions of sclerotium melanization in Botrytis cinerea. (April 2017) - Zhu, Pinkuan; Li, Qin; Zhang, Chenghua; Na, Yantao; Xu, Ling
Abstract: The sclerotium is a highly melanized dormant structure that plays an important role in the survival of many types of fungi. In Botrytis cinerea, the polyketide synthase gene, Bcpks12, was exclusively required for the melanization of sclerotia that are specifically expressed during sclerotial development. The albino sclerotia of Δ bcpks12 mutants produced in this study displayed hypersensitivity to external stressors, including extreme temperatures, oxidative chemicals, and desiccation. During the sclerotial development process, the initial sclerotia of the wild-type strain secreted novel liquid droplets on the surfaces, although these exudates gradually disappeared as the sclerotia became deeply pigmented with melanin. In contrast, the exudates accumulated and remained on the surface of the non-melanized sclerotia produced by the Δ bcpks12 mutants. The sclerotial liquid exudates were confirmed to contain nutrients and effectively stimulate spore germination. This combination of results substantiates the hypothesis that melanin pigmentation is necessary for the maturation of fungal sclerotia, which thus terminates the secretion of nutrition-rich exudates and seems to be essential to sclerotial survivability through adverse conditions. Highlights: Bcpks12 of Botrytis cinerea is exclusively required for melanization of sclerotia. Tolerance of sclerotia against external stressors is dependent on melanin. Melanin accumulation synchronizes with exudates decrease during sclerotial maturation. Sclerotial melanin is involved in terminating the secretion of nutrition-rich exudates.